1997
DOI: 10.1097/00006534-199712000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Care following CO2 Laser Resurfacing: Avoiding Pitfalls

Abstract: Facial skin resurfacing using the carbon dioxide laser has become an increasingly popular procedure. Improvements in carbon dioxide laser technology have made the procedure simpler and more reliable. However, difficulties in the postoperative period can lead to patient morbidity and physician anxiety. Common problems such as prolonged erythema, hyperpigmentation, acne, milia, dermatitis, and infection can be controlled or avoided with proper postoperative care. Less common sequela such as hypertrophic scarring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 16 publications
1
50
0
2
Order By: Relevance
“…17 It is unclear, however, if prophylaxis is needed for resurfacing procedures involving single cosmetic units of the face. 17 It is unclear, however, if prophylaxis is needed for resurfacing procedures involving single cosmetic units of the face.…”
Section: Discussionmentioning
confidence: 99%
“…17 It is unclear, however, if prophylaxis is needed for resurfacing procedures involving single cosmetic units of the face. 17 It is unclear, however, if prophylaxis is needed for resurfacing procedures involving single cosmetic units of the face.…”
Section: Discussionmentioning
confidence: 99%
“…Weinstein et al 27 suggested that removal of the epidermis alters the normal barrier function of the skin. Weinstein et al 27 suggested that removal of the epidermis alters the normal barrier function of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…17,29,45 Clinical evidence supports the use of such dressings after carbon dioxide (CO 2 ) laser skin resurfacing. 46,47 Topical medications are commonly utilized for abraded wounds and after wound closures. Eaglestein and Mertz noted the effect of various medications on the relative rate of healing.…”
Section: Wound Desiccationmentioning
confidence: 99%